Socioeconomic Profile of Early Childhood Education Preservice Teachers - (:unkn) unknown (My University, 2018)
Purpose: Teachers are key determiners of qualityeducation, and regarding young children inparticular, the quality of teachers can have a remarkable influence on the quality of education. However, research on the socioeconomic profile of preservice teachers at university remains rare in Turkey, especially eastern Turkey, where living conditions are below of the national average. In our study, the socioeconomic profile of 2,115 early childhood teacher candidates in faculties of education at state universities in the Eastern andSoutheastern Anatolian Regions of Turkey wasexamined. The study aimed to determine the rankorder of students’ preferred early childhoodeducation bachelor programs and the reasons fortheir preferences.Methods: The descriptive profile research sought to identify the socioeconomic profile ofpreservice early childhood teachers recruited from 11 state universities. Participating studentswere asked several questions concerning the socioeconomic aspects of their university life infour domains: demographic and economic characteristics, education budget, familysocioeconomic composition, and educational and sociocultural background. Descriptiveanalyses were performed to analyze the data. Results: The findings revealed that the studentswere mostly from low-income families. Most students ranked an early childhood educationbachelor program among their top five choices on university selection exams. The top threereasons for their choosing early childhood education as a profession were love for childrenand the profession, the convenience of teacher appointment and satisfactory wage levels atstate preschools, and the convenience and enjoyment of preschool teaching. Implications forResearch and Practice: Most students were members of low-income families, for whom social,cultural, and sportive activities need to be more accessible. Similar studies should be repeatedin other geographical regions of Turkey with students from other university departments andfaculties in order to clarify the socioeconomic composition of university students, developmore effective bachelor programs, and improve student life at Turkish universities.
Keywords: Eğitim, Eğitim Araştırmaları